(untitled) (Research, Society and Development, 2023)
Hyperdontia is a number anomaly in which the patient has an exceeded number of teeth, which are called supernumerary, and can appear both in deciduous dentition and in permanent dentition, which is the most common. Supernumerary teeth may have an anatomy that is the same or different from the normal dentition, such as a conical shape, for example, and may cause aesthetic or occlusal problems. The correct etiology of this anomaly is not known, may be due to odontogenesis failures or multifactorial. This work aims to demonstrate the prevalence of supernumerary teeth through the analysis of panoramic radiographs from a radiological clinic in the city of Viçosa. A total of 883 panoramic radiographs of patients aged between 7 and 15 years of both genders were analyzed. Of all the radiographs analyzed, 17 patients had supernumerary teeth, in which 8 were female and 9 were male. A total of 23 supernumerary teeth were found, and it was more common for patients to have only one supernumerary tooth in the arch. However, they may also have two or more supernumerary teeth, which were found in only 4 panoramic radiographs. Furthermore, there were no significant differences in the prevalence of this anomaly in relation to males and females. It can be concluded that this number anomaly is not very common, however, among the supernumerary teeth found, the most common was the “mesiodens”. In addition, as for the gnathic bones, the maxilla had a higher prevalence, specifically in the anterior region.